Adult Education: Organizational Approaches Under Uncertainty - Voino-Danchyshyna , O. (New Collegium, 2021)
Education, undoubtedly, is recognized as determining the social configuration of each state. Most countries of the world are intensively developing and improving the adult education system as an important element of lifelong learning that ensures the development of society. The concept of lifelong education is viewed as a system of the future, which should become the basis for sustainable development, ensuring stability in society, socialization of a person in a changing social environment. Globalization world processes also have a significant impact on education. At the same time, individual education systems should take into account national and cultural characteristics when developing adult education programs so that universalization is combined with existing diversity. The article analyzes the main directions of adult education such as obtaining a second higher education, business education and training for people of the third age. The specifics of the adult audience, the specifics of the work of teachers, the content of curricula and teaching methods are considered. When writing the article, the experience of working with adults, accumulated at the People's Ukrainian Academy, which is a complex of continuous education, in which the adult education system is logically inscribed, was used and generalized. The need to improve the national system of postgraduate education is expressed. We are talking about creating a unified regulatory framework for adult education, changing sectoral legislation, optimizing the structure of additional postgraduate education.